Perancangan dan Pembuatan Sistem Informasi Data Kependudukan Pada Desa Suka Mandi Hulu dengan menggunakan Visual Basic Net - Rivan Fatriyadi (PT. ALHAFI BERKAH INDONESIA, 2025)
Village government offices have various vital roles in processing government data such as population data. Data processing at the Suka Mandi Hulu Village Government Office still uses a semi-manual system, resulting in a lack of time efficiency in services and reporting. This problem motivates the author to create a population information system that can process population, family, birth, death, move-in, move-out data, cover letters and marriage certificates. This system is expected to support the performance of village officials in serving, processing and reporting population data. This village population information system was built using a visual basic development program for report design and uses a client-server network architecture. Creation begins with database design and output design, then continues with display creation and program code creation. The population information system created can speed up the process of providing population letters and managing population data and make it easier to present population data reports to the relevant agencies. This system is also used to import and export population data from and into Excel files and can support the performance of village officials, especially the village secretary and general head.